Effect of sonication on the technofunctional properties of L. mutabilis & L. angustifolius in wheat-based and gluten-free breads - Kärkkäinen, Emilia (My University, 2025)
As climate change impacts global food networks, a demand for more sustainable plant-based products has increased. Traditionally this category has been dominated by soybeans and products thereof, but an emerging new crop of lupine has garnered interest for its high protein content and other beneficial nutritional aspects. A downside to lupine is a potentially poisonous alkaloid content and poor technofunctional properties limiting its usage in multitude of food matrices. The aim of this study was to investigate whether ultrasound treatment could improve technofunctional properties of Lupinus mutabilis and Lupinus angustifolius and to test their suitability in wheat- and gluten-free breads. Both raw flours were sonicated and investigated for their technofunctional properties via FT-IR, water and oil absorption, Mixolab-analysis and others to visualize change induced by sonication. These were then baked into wheat- and gluten-free bread formulations and the differences between each lupine formulation was analysed using colour, specific volume, alveolar structure and texture profile analysis. Main results indicate that the effects of sonication are highly dependent on the lupine variety, since the technofunctional properties of L. angustifolius improved while those of L. mutabilis worsened in multiple categories. Further research on protein conformation is needed, since it is an important aspect for technofunctional properties. Any lupine addition to gluten-free formulation improved texture parameters while it worsened wheat formulations. Since lupine is incredibly nutritious, further research into adopting lupine to versatile food matrices is needed.
Keywords: sonication, Lupinus mutabilis, Lupinus angustifolius, gluten-free bread